Study on Chlorinated Gas Adsorption Using Activated Carbon via Polyvinyl Chloride (PVC) Stepwise Pyrolysis Process - Patiparn Boonruam; Piyachat Wattanachai; Settakorn Upasen (Proceedings, 2018)
In this research, we studied the chlorinated gas adsorption process using activated carbon. Two types of granular activated carbon were employed: GAC800 and GAC1200; with specific surface areas of 800 m2/g and 1200 m2/g, respectively. In order to optimize the polyvinyl chloride (PVC) dehydrochlorination conditions, three parameters were studied: (i) the type of precursor—PVC and PVC mixed with charcoal (1:1 by weight)—(ii) the temperature—300 and 400 °C—and (iii) the retention time—30, 120, and 240 min. Mohr’s method and acid-base titration were used to estimate the captured amount of chlorinated gas. The results indicated that the PVC dehydrochlorination occurred completely about 69–73 wt.% at 400 °C for 240 min. The amount of chloride ion was detected around 1–2 mmol/LNaOH. The estimated HCl adsorption capacity for the GAC800 and GAC1200 samples potentially absorbed 0.27 mgHCl/gGAC and 0.21 mgHCl/gGAC, respectively. In addition, the efficiency for GAC800 and GAC1200 was reported to 37.95% and 28.92%, respectively.